The Effect of NaOH Concentration and Acetylation Time on Synthesis of Kepok Banana Peel Cellulose Acetate - Yasmin, Fia Kharisma; Pramita, Ayu; Satriawan, Dodi (Universitas PGRI Madiun, 2023)
The high production of kepok banana is generating a significant amount of peel waste, contributing to environmental pollution. To address this issue, an innovative solution is the conversion of kepok banana peel into cellulose acetate as raw material for membrane production. Therefore, this research aimed to manufacture kepok banana peel cellulose acetate using varying concentrations of 1%, 1.5%, and 2% NaOH solvent, with acetylation times of 2 hours and 2.5 hours, respectively. The optimal results were achieved using 1% NaOH with kepok banana peel cellulose content of 56.07%. Furthermore, the best acetylation time occurred at a duration of 2.5 hours, producing a cellulose acetate content of 38.23% and a 2.3% degree of substitution (DS). These results suggested that the optimal combination for producing membrane from kepok banana peel is 1% concentration with an acetylation time of 2.5 hours, classifying it as cellulose diacetate.